Convergence of Colonial Politics, Islamic Ideology, and Popular Resistance: An Analysis of the Background of the Aceh War (1873-1903) - Airlangga, Zetira Novian; Akbar, Ichsan Kurnia; Lingga, Wahyu Rafael; Maler, Wani; Narny, Yenny (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2025)
The Aceh War (1873-1903) was one of the most critical and protracted armed conflicts in the history of Dutch colonialism in the Indonesian archipelago. This article aims to examine the background of the Aceh War through a thematic approach to three key aspects: colonial political expansion, the influence of Islamic ideology, and community participation, as manifested in the